M.leprae Positivity Comparison in PCR Assay Using Slit Skin Smear and Blood Specimen from New Case Leprosy Patients - R.Varidianto Yudo Tjahjono, - (2008)
Leprosy is a disease caused by Mycobacterium leprae. This disease can lead to abnormalities or deformities especially on extrimities. The diagnosis of leprosy is still based on clinical appearance and bacteriological finding, which are very subjective, less sensitive and less specific. To increase sensitivity and specifity on detecting M.leprae many authors developed Polymerase Chain Reaction (PCR) technique. This study will explore comparativeness between PCR using slit skin specimen against blood specimen. This study was performed on a new leprosy patients visited Department of Skin and Venereology, Dr.Soetomo Hospital Surabaya, from October until December 2007, by cross sectional approach. The aim of this study is to find out the difference in PCR technique using slit skin specimen and blood specimen. All included samples were taken as follow : 1) slit skin from lesion in the body surface; and 2) venous blood specimen. The result from 30 samples, 25 samples were leprosy patients MB type and 5 samples were PB type. Comparison in PCR technique using slit skin specimen against blood specimen in both MB type and PB type show significant difference (p=0.001; p < 0.05). As many as 66,7% (20 of 30 samples) slit skin specimens and 20% (6 of 30 samples) blood specimens were positive. The positivity comparison beetween slit skin specimens and blood specimens were 3.3 : 1. This result show that PCR technique using slit skin specimens seems to be more sensitive than PCR technique using blood specimens for diagnosis of leprosy respectively.